Five [compact disc] - Prince Royce (Sony Music Latin, 2017)
Combining tropical and mainstream sounds with poetic lyrics, Prince Royce has taken the music world by storm. His latest promises to be his most powerful yet and features appearances from Zendaya, Farruko, and more.